The cognitive nexus between Bohr's analogy for the atom and Pauli's exclusion schema. Issue 1 (March 2016) - Ulazia, Alain
Highlights: I examine the mental schema of Bohr's atomic model and Pauli's exclusion principle from a historical-cognitivist view. The correspondence principle was an analogical principle which activated powerful schemas. Bohr's images and subsequent analogies had non-classical epistemic components which were able to evoke the idea of exclusion as a prohibition law. The intervention of analogy and mental schemas was fruitful. These schematic ideas are essential in the construction of branches of mathematics and consequently of physics. Abstract : The correspondence principle is the primary tool Bohr used to guide his contributions to quantum theory. By examining the cognitive features of the correspondence principle and comparing it with those of Pauli's exclusion principle, I will show that it did more than simply 'save the phenomena'. The correspondence principle in fact rested on powerful analogies and mental schemas. Pauli's rejection of model-based methods in favor of a phenomenological, rule-based approach was therefore not as disruptive as some historians have indicated. Even at a stage that seems purely phenomenological, historical studies of theoretical development should take into account non-formal, model-based approaches in the form of mental schemas, analogies and images. In fact, Bohr's images and analogies had non-classical components which were able to evoke the idea of exclusion as a prohibition law and as a preliminary mental schema.